(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In EFL (English as a Foreign Language) contexts, classical teaching methods such as the Audio-Lingual Method (ALM) and Total Physical Response (TPR) have long histories but are often overlooked in favor of communicative and task-based approaches. This article compares ALM and TPR, exploring their theoretical foundations, strengths and weaknesses, and how they can be adapted for modern multilingual classrooms. Drawing on recent empirical studies (especially from 2021–2025), the discussion shows how ALM’s emphasis on habit formation and drill complements TPR’s embodied learning and kinesthetic involvement. The comparison is enriched by classroom reflections illustrating how a hybrid approach can balance accuracy and fluency, reduce learner anxiety, and increase engagement. Implications for teacher practice, curriculum design, and assessment are offered.